Conjugation across Bacillus cereus and kin: A review - Hinnekens, Pauline; Fayad, Nancy; Gillis, Annika; Mahillon, Jacques (Frontiers in Microbiology, 2022)
Horizontal gene transfer (HGT) is a major driving force in shaping bacterial communities. Key elements responsible for HGT are conjugation-like events and transmissible plasmids. Conjugative plasmids can promote their own transfer as well as that of co-resident plasmids. Bacillus cereus and relatives harbor a plethora of plasmids, including conjugative plasmids, which are at the heart of the group species differentiation and specification. Since the first report of a conjugation-like event between strains of B. cereus sensu lato (s.l.) 40 years ago, many have studied the potential of plasmid transfer across the group, especially for plasmids encoding major toxins. Over the years, more than 20 plasmids from B. cereus isolates have been reported as conjugative. However, with the increasing number of genomic data available, in silico analyses indicate that more plasmids from B. cereus s.l. genomes present self-transfer potential. B. cereus s.l. bacteria occupy diverse environmental niches, which were mimicked in laboratory conditions to study conjugation-related mechanisms. Laboratory mating conditions remain nonetheless simplistic compared to the complex interactions occurring in natural environments. Given the health, economic and ecological importance of strains of B. cereus s.l., it is of prime importance to consider the impact of conjugation within this bacterial group.